Electrochemical CO2 reduction in water at carbon cloth electrodes functionalized with a fac-Mn(apbpy)(CO)3Br complex. Issue 6 (19th December 2018) - Rotundo, Laura; Filippi, Jonathan; Gobetto, Roberto; Miller, Hamish A.; Rocca, Riccardo; Nervi, Carlo; Vizza, Francesco
Abstract : The carbon-cloth-supported organometallic complex ( fac -Mn(apbpy)(CO)3 Br) reduces CO2 to syngas in aqueous media with a FE of 60% and a TON of up to 33 200. Abstract : The organometallic complex ( fac -Mn(apbpy)(CO)3 Br) (apbpy = 4-(4-aminophenyl)-2, 2′-bipyridine) grafted electrochemically onto carbon cloth serves as an electrocatalyst in the aqueous reduction of CO2 to syngas. A faradaic efficiency of around 60% for CO and 40% for H2 at −1.35 V is achieved together with a productivity rate higher than 870 NlCO h −1 gMn −1 at turnover numbers of up to 33 200 during 10 hours of operation.